Association of Progressive Cerebellar Atrophy With Long-term Outcome in Patients With Anti-N-Methyl-d-Aspartate Receptor Encephalitis - lizuka, Takahiro (JAMA Neurol, 2016)
IMPORTANCE: Anti-N-methyl-d-aspartate receptor (NMDAR) encephalitis is an immune-mediated disorder that occurs with IgG antibodies against the GluN1 subunit of NMDAR. Some patients develop reversible diffuse cerebral atrophy (DCA), but the long-term clinical significance of progressive brain and cerebellar atrophy is unknown. OBJECTIVE: To report the long-term clinical implications of DCA and cerebellar atrophy in anti-NMDAR encephalitis. DESIGN, SETTING, AND PARTICIPANTS: A retrospective observational study and long-term imaging investigation was conducted in the Department of Neurology at Kitasato University. Fifteen patients with anti-NMDAR encephalitis admitted to Kitasato University Hospital between January 1, 1999, and December 31, 2014, were included; data analysis was conducted between July 15, 2015, and January 18, 2016. EXPOSURES: Neurologic examination, immunotherapy, and magnetic resonance imaging (MRI) studies were performed. MAIN OUTCOMES AND MEASURES: Long-term MRI changes in association with disease severity, serious complications (eg, pulmonary embolism, septic shock, and rhabdomyolysis), treatment, and outcome. RESULTS: The clinical outcome of 15 patients (median age, 21 years, [range, 14–46 years]; 10 [67%] female) was evaluated after a median follow-up of 68 months (range, 10–179 months). Thirteen patients (87%) received first-line immunotherapy (intravenous high-dose methylprednisolone, intravenous immunoglobulin, and plasma exchange alone or combined), and 4 individuals (27%) also received cyclophosphamide; 2 patients (13%) did not receive immunotherapy. In 5 patients (33%). ovarian teratoma was found and removed. Serious complications developed in 4 patients (27%). Follow-up MRI revealed DCA in 5 patients (33%) that, in 2 individuals (13%), was associated with progressive cerebellar atrophy. Long-term outcome was good in 13 patients (87%) and poor in the other 2 individuals (13%). Although cerebellar atrophy was associated with poor long-term outcome (2 of 2 vs 0 of 13 patients; P = .01), other features, such as DCA without cerebellar atrophy, serious complications, ventilatory support, or prolonged hospitalization, were not associated with a poor outcome. Five patients with DCA had longer hospitalizations (11.1 vs 2.4 months; P = .002), required ventilatory support more frequently (5 of 5 vs 4 of 10 patients; P = .04), and developed more serious complications (4 of 5 vs 0 of 10 patients; P = .004) compared with those without DCA. Although DCA was reversible, cerebellar atrophy was irreversible. CONCLUSIONS AND RELEVANCE: In anti-NMDAR encephalitis, DCA can be reversible and does not imply a poor clinical outcome. In contrast, cerebellar atrophy was irreversible and associated with a poor outcome. This observation deserves further study to confirm progressive cerebellar atrophy as a prognostic marker of poor outcome.